Using Short‐lived Radionuclides to Estimate Rates of Soil Motion in Frost Boils. (26th June 2014) - Klaminder, J.; Yoo, K.; Olid, C.; Ramebäck, H.; Vesterlund, A.
ABSTRACT Cryoturbation in high‐latitude soils is crucial for the long‐term cycling of elements, but the rates of soil motion are poorly constrained. Here, we test whether the rate of frost creep, soil erosion and vertical soil mixing in frost boils can be estimated using short‐lived radionuclides (137Cs and 210Pb). We find a small‐scale variation in 137Cs and 210Pb inventories in the lower levels of the eroding regions of frost boils in comparison to the expected depositional sites; hence, the distribution of the radionuclides appears to reflect a lateral transport of atmospheric fallout from the centre of the boil (inner domain) towards the surrounding soil (outer domain). 14C dating of the soil indicates that fallout of 137Cs was mobile in the soil and that 210Pb moved with the soil matrix. A soil creep model and a surface soil erosion model are derived and applied to the lateral and vertical distributions of 210Pb in the frost boil. Both models predict the expected trajectories of soil motion and provide rates of creep, erosion and mixing at a mm yr−1 to cm yr−1 scale. The distribution of 210Pb provides new insights about the processes and rates of soil mass movement in frost boils, if sound mass‐balance models are applied. Copyright © 2014 John Wiley & Sons, Ltd.